Pengaruh Terapi Musik Klasik (Mozart) Kombinasi Dengan Kompres Hangat KOMBINASI DENGAN KOMPRES HANGAT UNTUK MENURUNKAN TEKANAN DARAH PENDERITA HIPERTENSI - Yora Nopriani; Cindi Lia Ariska (LPPM STIKes Mitra Adiguna, 2022)
Background: According to data from the World Health Organization (WHO), around 972 million people worldwide or 26.4% of people in the world suffer from hypertension. Handling hypertension and complications due to hypertension can be done pharmacologically and non-pharmacologically. Pharmacological therapy for hypertensive patients should be combined with non-pharmacological therapies such as a healthy diet, weight control, and regular exercise, relaxation exercises, yoga, meditation. Objective: to determine the effect of classical music therapy (Mozart) in combination with warm compresses on reducing blood pressure in hypertensive patients. Methods: The research design used in this study was a two group pretest and posttest design. This research was conducted on 16 – 31 May 2022. The population in this study were 30 hypertension sufferers at the Harapan Kita Social Institution in Palembang, the sampling technique used purposive sampling with a sample of 30 respondents who were divided into 2 groups, namely the intervention group and the control group. . Collecting data using observation. Data analysis used univariate and bivariate analysis. Result: there is an effect of classical music therapy (Mozart) in combination with warm compresses on decreasing blood pressure (p value = 0.002 and 0.000). Suggestion: it is hoped that it can be an additional reference that can be used as an alternative action/therapy in a non-communicable disease control program, namely hypertension. Keywords: Hypertension, Classical Music, Warm Compress